Crystal structures of T. b. rhodesiense adenosine kinase complexed with inhibitor and activator: implications for catalysis and hyperactivation. - Sabine Kuettel; Jason Greenwald; Dirk Kostrewa; Shaheen Ahmed; Leonardo Scapozza; Remo Perozzo (Public Library of Science (PLoS), 2011)
BACKGROUND: The essential purine salvage pathway of Trypanosoma brucei bears interesting catalytic enzymes for chemotherapeutic intervention of Human African Trypanosomiasis. Unlike mammalian cells, trypanosomes lack de novo purine synthesis and completely rely on salvage from their hosts. One of the key enzymes is adenosine kinase which catalyzes the phosphorylation of ingested adenosine to form adenosine monophosphate (AMP) utilizing adenosine triphosphate (ATP) as the preferred phosphoryl donor. METHODS AND FINDINGS: Here, we present the first structures of Trypanosoma brucei rhodesiense adenosine kinase (TbrAK): the structure of TbrAK in complex with the bisubstrate inhibitor P(1),P(5)-di(adenosine-5')-pentaphosphate (AP5A) at 1.55 Å, and TbrAK complexed with the recently discovered activator 4-[5-(4-phenoxyphenyl)-2H-pyrazol-3-yl]morpholine (compound 1) at 2.8 Å resolution. CONCLUSIONS: The structural details and their comparison give new insights into substrate and activator binding to TbrAK at the molecular level. Further structure-activity relationship analyses of a series of derivatives of compound 1 support the observed binding mode of the activator and provide a possible mechanism of action with respect to their activating effect towards TbrAK.